Penciptaan Lakon Pancakusuma Labuh dalam Upaya Penyampaian Nilai-nilai Keteladanan Seorang Negarawan - Mukti Wicaksono, Muhammad Setyo Mukti Wicaksono; Harti, Sri (Institut Seni Indonesia Surakarta, 2023)
Pancakusuma Labuh is a creation that raises the issue of nationalism with the figure of Pancakusuma. The creation of this work aims to offer ideas as a mirror of life that upholds exemplary values in the life of the nation and state. Moreover, this creation intends to increase the vocabulary of garap lakon Pakeliran. In the process of creating, the creators use the concept of pakeliran padat and the aesthetic concept of nuksma and mungguh as a frame for the performance. To create the artwork of Pancakusuma Labuh, Alma Hawkins’ method of work creation was used, that is exploration, improvisation, and creation of artworks. The result of this artistic work is a wayang kulit performance lakon Pancakusuma Labuh which actualizes exemplary values in the form of nationalism values, bawalaksana values, and dedication values.